Sestrin 2 Attenuates Rat Hepatic Stellate Cell (HSC) Activation and Liver Fibrosis via an mTOR/AMPK-Dependent Mechanism - Yi-Bing Hu; Xiao-Ting Ye; Qing-Qing Zhou; Rong-Quan Fu (Cellular Physiology and Biochemistry, 2018)
Background/Aims: Sestrin 2 is associated with the pathophysiology of several diseases. The aim of this study was to investigate the effects and potential mechanisms of Sestrin 2 in rat hepatic stellate cells (HSCs) during liver fibrogenesis. Methods: In this study, Sestrin 2 protein expression was detected in rat HSC-T6 cells challenged with transforming growth factor-β (TGF-β) and in mice treated with carbon tetrachloride (CCl4), a well-known model of hepatic fibrosis. Next, HSC-T6 cells and fibrotic mice were transfected with lentivirus. The mRNA expression levels of markers of liver fibrosis [alpha-smooth muscle actin (α-SMA) and collagen 1A1 (Col1A1)] were analyzed by quantitative reverse transcription–polymerase chain reaction (RT-PCR). Cell death and proliferation were evaluated by the MTT assay, and biochemical markers of liver damage in serum [alanine transaminase (ALT) and aspartate transaminase (AST)] were also measured using a biochemical analyzer. Histopathological examination was used to evaluate the degree of liver fibrosis, and protein expression [phospho-adenosine monophosphate-activated protein kinase (p-AMPK), AMPK, phospho-mammalian target of rapamycin (p-mTOR), and mTOR] was determined by western blotting. Results: We found that Sestrin 2 was elevated in both the HSC-T6 cell and hepatic fibrosis models. In vitro, overexpression of Sestrin 2 attenuated the mRNA levels of α-SMA and Col1A1, suppressed α-SMA protein expression, and modulated HSC-T6 cell proliferation. In vivo, overexpression of Sestrin 2 reduced the ALT and AST levels as well as the α-SMA and Col1A1 protein expression in the CCl4 model of liver fibrosis. Moreover, the degree of liver fibrosis was ameliorated. Interestingly, overexpression of Sestrin 2 increased p-AMPK but decreased p-mTOR protein expression. Conclusion: Our findings indicate that Sestrin 2 may attenuate the activation of HSCs and ameliorate liver fibrosis, most likely via upregulation of AMPK phosphorylation and suppression of the mTOR signaling pathway.